Synthesis and biological comparison of two antimicrobial peptides originated from the venom of Vespa crabro and Polybia paulista - Le Huy Binh,; Bui Thi Phuong Hai,; Do Hai Yen,; Trinh Thi Kim Anh,; Nguyen Hong Minh,; Nguyen Thi Thanh Binh,; Luong Xuan Huy,; Vu Dinh Hoang, (Vietnam Journal of Science and Technology, 2024)
Mastoparan C and Polybia-MP1 are two well-known AMPs found in the European Hornet Vespa crabro and social wasåp Polybia paulista, respectively. Due to the potent antimicrobial activity toward a wide range of microbial pathogens, including Gram-negative, Gram-positive and fungal species, they are promising to tackle the global antimicrobial resistance crisis. Thus, understanding the structure and activity relationships (SARs) is essential for the development of potential therapeutic applications. In this study, we prepared Mastoparan C and Polybia-MP1 and investigated the differences in their biological properties. Both AMPs were successfully synthesized and purified with more than 95% purity, confirmed by high-performance liquid chromatography and mass spectrometry. Besides, the data indicated a decrease in antimicrobial activity but notably less hemolysis of MP1 compared to MPC. Overall, our study suggests various important information regarding the structural requirements for the antimicrobial and hemolytic activity of antimicrobial peptides.